The Use of Antiviral Drugs for Influenza: Recommended Guidelines for Practitioners - Upton D Allen; Fred Y Aoki; H Grant Stiver; for the Canadian Paediatric Society and the Association of Medical Microbiology and Infectious Disease Canada (Canadian Journal of Infectious Diseases and Medical Microbiology)
The present document outlines current guidelines and supporting literature relating to the use of antiviral drugs for chemoprophylaxis and influenza illness therapy in paediatric and adult settings. The focus is on the management of influenza in interpandemic periods. Where appropriate, the areas in need of additional research are identified. It will be necessary to update aspects of these guidelines as new information emerges. The recommendations that follow represent the results of a joint effort supported by the Canadian Paediatric Society and the Association of Medical Microbiology and Infectious Disease Canada.